Sosio Kultural Masyarakat Daerah Tepian Sungai Kapuas Tanjung Hilir terkait Stunting - Desi Desi; Ismi Trihardiani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The occurrence of stunting in toddlers is often unnoticed, and after two years, it is seen that the toddler is short. Chronic nutritional problems in toddlers are caused by poor nutritional intake for a long time due to parents/families do not know or are not aware to provide food that suits their child's nutritional needs. The purpose of this research is to provide an overview of the sociocultural community that forms the understanding of toddler mothers about stunting, consumption patterns, personal and hygienic parenting patterns, and the environment of the Kapuas riverbank area of Tanjung Hilir Pontianak City. The research method is Qualitative Research using a Descriptive research design. The sample in this study was 40 toddlers aged 24-59 months. Sampling techniques using purposive sampling method, Data analysis is done descriptively. The study results obtained fostering patterns in toddlers' normal nutritional status, and stunting nutritional status has the same parenting pattern. Feeding children in a day less than three times a day in toddlers stunting nutritional status. Environmental sanitation or hygiene assessment in the Kapuas Tanjung Hilir River Bank area showing an unhealthy environment. Conclusion There are differences in usage that form the mother's understanding of stunting, consumption patterns, parenting patterns, and personal and environmental hygiene in the Kapuas Tanjung Hilir River Bank area.